2017
DOI: 10.4007/annals.2017.185.1.6
|View full text |Cite
|
Sign up to set email alerts
|

A sharp counterexample to local existence of low regularity solutions to Einstein equations in wave coordinates

Abstract: We give a sharp counter example to local existence of low regularity solutions to Einstein's equations in wave coordinates. We show that there are initial data in H 2 satisfying the wave coordinate condition such that there is no solution in H 2 to Einstein's equations in wave coordinates for any positive time. This result is sharp since Klainerman-Rodnianski and Smith-Tataru proved existence for the same equations with slightly more regular initial data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…To prove ill-posedness for (1.1), as in [3,16,30,31], we work under planar symmetry. And the solution satisfies U(x 1 , x 2 , x 3 , t) = U (x 1 , t).…”
Section: Decomposition Of Wavesmentioning
confidence: 99%
See 2 more Smart Citations
“…To prove ill-posedness for (1.1), as in [3,16,30,31], we work under planar symmetry. And the solution satisfies U(x 1 , x 2 , x 3 , t) = U (x 1 , t).…”
Section: Decomposition Of Wavesmentioning
confidence: 99%
“…Under planar symmetry, Lindblad gave sharp counterexamples to the lowregularity local well-posedness for semilinear and certain quasilinear wave equations in [29][30][31]. In [16], Ettinger-Lindblad generalized the above results to the Einstein's equations and constructed a sharp counterexample for local well-posedness of Einstein vacuum equations in wave coordinates. An exploration by Granowski [17] later showed that Lindblad's H s ill-posedness in [31] is stable under general perturbations.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to the stability problem of Minkowski space, spacetime harmonic gauge is also used in the context of the cosmological stability problem by [12,13]. In addition to these examples, there are numerous other studies (e.g., [14,15,16]) that utilize this particular choice of gauge. Andersson and Moncrief [18] proved an asymptotic stability result of the Milne universe utilizing the CMCSH gauge.…”
Section: Introductionmentioning
confidence: 99%
“…is ill-posed in H 2 (see also Lindblad [19], Ettinger and Linblad [4] for quasi-linear case). Then it is natural to expect (1.1) is ill-posed in H s l in general when 2 ≤ p ≤ 1 + 4 n−1 .…”
Section: Introductionmentioning
confidence: 99%